Study of different types of synchronization in chaotic systems - González Villacorte, Mabel Alejandra (2022)
This work focuses on the study of synchronization between chaotic dynamical systems. In this proposal, starting from a general system we aim, by considering particularities, to identify and study two types of synchronization: complete and partial. We present a novel strategy to analyze the synchronization of nonlinearly coupled dynamic systems. The usual methods considered rely on finding Lyapunov functions or studying Lyapunov exponents; however, we restrict this work to autonomous systems, therefore, reducing the problem of establishing synchronization to studying the eigenvalues of the matrix associated with the system. Moreover, we illustrate the theoretical results by highlighting and recreating different examples of synchronization in well-known chaotic non-linear dynamical systems from relevant literature.